Diffuse Idiopathic Skeletal Hyperostosis Extended to the Lumbar Segment Is a Risk Factor of Reoperation in Patients Treated Surgically for Lumbar Stenosis. Issue 20 (15th October 2018) - Yamada, Kentaro; Satoh, Shigenobu; Abe, Yuichiro; Yanagibashi, Yasushi; Hyakumachi, Takahiko; Masuda, Takeshi
Abstract : Study Design: Retrospective longitudinal cohort study. Objective: To investigate the association between diffuse idiopathic skeletal hyperostosis (DISH) and reoperation in patients treated surgically for lumbar spinal stenosis (LSS) in long-term results. Summary of Background Data: Few studies have evaluated DISH as a potential risk factor of poor surgical results for LSS. Methods: This study included 1063 responders to a postoperative postal survey out of 2363 consecutive patients who underwent surgery for LSS between 2002 and 2010. The survey included questions about reoperations performed at another hospital and the patient-reported outcomes. DISH was evaluated by preoperative standing whole-spine radiographs. We investigated DISH as a predictor of reoperation and characteristics of poor outcomes in patients with DISH. We also assessed selection bias by examining the differences between responders and nonresponders to a postal survey. Results: Reoperations were performed in a total of 115 patients (10.8%) within an average of 8.6 years after the initial surgeries. Patients who only had DISH were not associated with reoperation; however, reoperations were performed significantly more often in patients with DISH extended to the lumbar segment (L-DISH) than in patients without (22% and 7.3%, respectively; P  < 0.001). Cox analysis showed that L-DISH was one of the significant independent predictors for reoperation (hazard ratio 2.05, P  = 0.009). Surgery-free survival was significantly shorter in patients with L-DISH than in those without ( P  = 0.005). The cause of reoperation did not differ between the patients with and without L-DISH. Several factors, but not L-DISH, were significantly associated with responders to the survey. Conclusion: L-DISH was independently associated with reoperation for LSS. The decreased number of lumbar mobile segments due to L-DISH might lead to unfavorable outcomes. Careful follow-up of patients is needed after surgery for LSS with L-DISH. Level of Evidence: 3